ANALISIS PREDIKSI JARAK DENGAN MENERAPKAN METODE PHASE ONLY CORRELATION PADA KAMERA STEREO - Suryaselaksa, Lukman Hakim; Rasmana, Susijanto Tri; Harianto, Harianto (Journal of Control and Network Systems (JCONES), 2016)
Nowadays 3D Technology growing so fast, it can be seen from many 3D products on the market. But unfortunately, 3D products on the market only used for entertainment. Whereas, 3D product can be used for something more functional, like a distance measurement. Normaly 3D measurement using a stereo camera, but the price of stereo camera is fairly expensive. By the way, the stereo camera functions can be replaced by two cameras that have been calibrated. The calibrated camera intended to obtain the characteristics of the stereo camera. Object captured by the two cameras that have been calibrated, to be processed using POC (Phase Only Correlation) method, and from the process can be known distance calculations.